Trade secrets law and corporate disclosure: Causal evidence on the proprietary cost hypothesis - LI, Yinghua (Institutional Knowledge at Singapore Management University, 2018)
This study exploits the staggered adoption of the inevitable disclosure doctrine (IDD) by U.S. state courts as an exogenous shock that generates variations in the proprietary costs of disclosure. We find that firms respond to IDD adoption by reducing the level of disclosure regarding their customers’ identities, supporting the proprietary cost hypothesis. Our results are stronger for firms in industries with a higher degree of entry threats, for firms in more volatile industries, and for firms with a lower degree of external financing dependence. Overall, this study represents one of the first efforts in identifying the causal effect of proprietary costs of disclosure on the supply of disclosure.